Peran Hukum Ekonomi Syariah Dalam Mengatur Transaksi Bisnis Syariah - Ade Zuki Damanik (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study discusses the role of Islamic economic law in regulating Islamic business transactions by emphasizing the principles of justice, transparency, and compliance with Islamic values. Islamic economic law functions to create Islamic regulations and guidelines that must be adhered to in every business transaction, prohibiting practices such as usury, maysir, and gharar. Within this framework, the principles of tauhid, khilafah, justice, tazkiyah, and al-falah become the main foundations underlying all economic activities. This study uses a qualitative method with a literature study to analyze various related literature sources. The main findings show that Islamic economic law not only provides a clear legal framework but also effectively prevents haram practices, resulting in fairer and more ethical transactions. The application of Islamic principles in business transactions can increase trust and stability in the Islamic business ecosystem. This study contributes in the form of concepts and methods that can be used to implement Islamic economic principles. The limitation of this study lies in its focus mainly on general theory and principles, while further research can explore more deeply the practical implementation of Islamic economic law in various business sectors. The implication of this study is the importance of education, regulatory development, and increasing transparency in business transactions to create a fairer and more sustainable business environment.